2001
DOI: 10.1002/cncr.9019
|View full text |Cite
|
Sign up to set email alerts
|

Critical clinicopathologic analysis of 23 cases of fine-needle breast sampling initially recorded as false-positive

Abstract: BACKGROUND Because false‐positive cytologic diagnoses in breast tumors are rare, few cases have been reported, although their consequences may be highly detrimental to the patient. The authors report the Institut Curie's experience, by using a multidisciplinary approach. METHODS Of 9334 benign breast tumors examined preoperatively for cytologic diagnosis by fine‐needle sampling (FNS), the 23 (0.25%) FNS cases considered to be false‐positive were retrospectively reviewed and analyzed. RESULTS Tumors were situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…guided. It can be assumed that large volume activity and learning through experience can lead to better results as seen in materials done previously at our Institut on palpable or nonpalpable breast lesions 1,32,33. Our results show that FNA performs better than CNB in PBTs giving less unsatisfactory results for malignant lesions as shown inTable 1.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…guided. It can be assumed that large volume activity and learning through experience can lead to better results as seen in materials done previously at our Institut on palpable or nonpalpable breast lesions 1,32,33. Our results show that FNA performs better than CNB in PBTs giving less unsatisfactory results for malignant lesions as shown inTable 1.…”
supporting
confidence: 65%
“…In our opinion, both methods (FNA and CNB) depend on the qualities of the sample, sampler, and the number of biopsies. It can be assumed that large volume activity and learning through experience can lead to better results as seen in materials done previously at our Institut on palpable or nonpalpable breast lesions 1,32,33. FNA and CNB are two techniques which should not be considered as two separate diagnostic methods but rather as two complementary methods 11,34.…”
mentioning
confidence: 99%
“…It has been shown that FP fine needle smears often represent peculiar types of breast lesions, such as papillomas, fat tissue necrosis, tubular adenomas, pregnancy‐ or radiation‐related changes and granulomas 22,23 . Klijanienko et al.…”
Section: False Positivesmentioning
confidence: 99%
“…FNA cytology should be combined with other clinical and radiologic diagnostic modalities, such as physical examination, ultrasonography and mammography. 21,22 …”
mentioning
confidence: 99%